Service production functions - Dietmar Lindenberger (Institute of Energy Economics at the University of Cologne (EWI), 2003)
The paper derives production functions designed to model the evolution of service industries. The derivation is based on specifying the output elasticities of the factors according to differential equations and asymptotic technological boundary conditions in factor space. The derived functional forms incorporate labor, capital, energy, and technological parameters, whose time changes model innovation and structural change. The model is applied to the evolution of the German market-determined services 1960-1989.
Keywords: O30; Q43; E23; 330; Production Factor Energy; Production Functions; Structural Change; Dienstleistungssektor; Produktionsfunktion; Energie; Schätzung; Deutschland